Econometric Analysis of Union Membership Growth in Canada, 1935-1981 - Kumar, Pradeep; Dow, Bradley (Relations industrielles / Industrial Relations, 1986)
The paper specifies an alternative model of union growth which builds on the strengths of the popular A/P andB/E models and incorporates several hypotheses relating aggregate union membership growth to changes in key business cycle variables, the legislative framework, and the inter-industry and male-female composition of the labour force.